Implications for High-intensity Aerobic Exercises on Omani Cardiorespiratory Endurance and Blood Lipids and Lipoproteins - Majid Al Busafi; Mahfoodha Al-Kitani; Ali Al-Mamari; Ehsan Mekki; Abdullah Al-Qaidi; Yogesh Sinha; Asharul Khan (College of Physical Education and Sport Sciences, 2023)
Background: Regular exercise provides benefits that are beyond dispute, and promoting physical activity levels ought to be a primary focus at all levels of healthcare. Chronic exercise causes a variety of cellular and organismal changes that modify how the body processes all macronutrients, including lipids. Purpose: The study investigates different types of aerobic exercise and their impact on both types of cholesterols-low-density-lipoprotein and high-density-lipoprotein cholesterol and recommends the best protocol for regulating cholesterol levels. Design/Methodology/Approach: This mixed-method study analyzes survey questionnaires distributed among physicians from two different sites in Oman. A total of 60 randomly selected and complete samples were used for the analysis using the Chi-square test. The survey consists of demographic information and questions about the types of cholesterol and types of aerobic exercise and the effect of different kinds of aerobic exercise on cholesterol levels. Finding: The study's findings demonstrate a statistically significant reduction of cholesterol levels through 20-30 minutes of aerobic exercise (walking, swimming, and running). The relationship between aerobic exercise and cholesterol levels vis-a-vis age and gender is not statistically significant. Furthermore, this study recommends the best protocol for regulating cholesterol levels. Research implications: The study has wider implications for future studies in wellness rhetoric in the Arab Gulf States. The outcome is on the wellness discourse which has mass level impact. The rhetoric of wellness programs has a buy-in potential for the Arab Gulf States sitting on the cusp of lifestyle-based diseases, including blood pressure and diabetes. Originality/value: With hardly any extant research in this field in Oman and some sporadic studies in Arab Gulf states, this study establishes its originality, exigency, and value addition in the repertoire of wellness programs in Oman and the Arab Gulf States.